EVALUATING THE OUTCOME OF STROKE: A PROSPECTIVE HOSPITAL BASED STUDY - Khan, Salma N.; Vohra, Ejaz Ahmad (Journal of Postgraduate Medical Institute, 2011)
Objective: This study was aimed to determine the functional outcome after stroke and to assess the influence of various factors on acute in-hospital stroke mortality. Material and Methods: This prospective study included 281 stroke patients of either sex, 20 to 70 years and above admitted in Dr. Ziauddin Medical University Hospital, North Nazimabad Campus, Karachi, during a period of one year. Main outcome measures used were Glasgow Coma Scale (GCS) and Modified Rankin Scale (mRS). Results: Data analysis showed that in-hospital mortality was 11.74% (n=33/281). Age and gender had no adverse effect on acute mortality in this study while poor initial GCS; hemorrhagic stroke and all the studied risk factors were bad prognostic factors. At the end of one month, 32 patients were lost to followup and mortality was 13.5% (n=5/216) while excellent outcome was observed in 22.27% (n=47/216) and poor outcome in 77.72% (n=164/216) of patients. Conclusion: This study confirms the significant morbidity and mortality associated with stroke and shows the need in preventing and controlling the risk factors for early death.